Technologies in Education Across the Americas : The Promise and the Peril – and Some Potential Ways Forward - Trucano, Michael (World Bank, Washington, DC, 2017)
New information and communication technologies (ICTs) have long been heralded around the world for their potential to 'revolutionalize' education. This has been true no matter the place or the specific technologies considered whether we are talking about early promises related to the use of television and radio in past decades or the laptops and tablets of today. Excitement around this 'transformative' potential is unlikely to subside in the near future: Devices will only get cheaper, and more powerful, in the coming years, and new technologies as yet un-invented will emerge to do things that were previously possible only in the realm of science fiction. That said, while connected computing devices like laptops, tablets and smartphones are increasingly to be found in the pockets and homes of many learners and teachers, slow-to-change formal education systems have led many people to observe that "technology is already revolutionizing education – just not in the classroom."